The Sexual Goals of Metoidioplasty Patients and Their Attitudes Toward Using PDE5 Inhibitors and Intracavernosal Injections as Erectile Aids. Issue 3 (8th April 2022) - Khorrami, Amir; Kumar, Sahil; Bertin, Elise; Wassersug, Richard; O'Dwyer, Cormac; Mukherjee, Smita; Witherspoon, Luke; Mankowski, Peter; Genoway, Krista; Kavanagh, Alex G.
Abstract: Background: Following metoidioplasty, transmen (TM) experience sexual function challenges including erectile dysfunction, which is typically treated in cisgender men with phosphodiesterase-5 inhibitors (PDE5i) and intracavernosal injections (ICI). Aim: We aim to evaluate sexual function post-metoidioplasty and explore attitudes toward using PDE5i and ICI as potential erectile aids Methods: All patients who had metoidioplasty completed at the Gender Surgery Program in Vancouver, British Columbia were contacted. Participants completed an electronically accessible self-constructed questionnaire consisting of 39 items on erectile function, orgasm, and penetrative intercourse which also captured Erection Hardness Scores (EHS). Data were analyzed via t -test and 1-way ANOVA. Outcomes: Our outcomes were the importance of erectile function, ability to orgasm, penetrative intercourse, and attitudes towards using PDE5i and ICI post-metoidioplasty. Results: Fifteen out of 22 patients completed the survey (median age 32 years). Most had metoidioplasty within the past 2 years. The participants ranked the ability to orgasm and to achieve or maintain erections significantly higher than penetrative intercourse ( P <.001, P =.005 respectively). Most participants reported facing challenges with penetrative intercourse (87%) and erectile function (80%). In contrast, a smaller proportion reported challenges with orgasm (33%). With regards to EHS, 83% of participants described their erections as either "larger but not hard, " or "hard but not hard enough for penetration." A total of 47% of the participants had previously tried PDE5i, but none had used ICI. Although 87% were willing to use PDE5i, only 40% were willing to try ICI to improve their erections. Patients reported lack of knowledge and understanding among primary care physicians as barriers to accessing treatment for sexual dysfunction. Clinical Translation: The results of this study can facilitate decision making for TM undergoing genital gender-affirmation surgery and provide potential options for improving erectile function post surgery. Strengths & Limitations: This study represents the first assessment of sexual function and use of erectile aids in post-metoidioplasty patients. The results of this study are limited by the small sample size and enrolment from a single surgical center. Conclusion: Metoidioplasty patients surveyed fail to achieve a fully rigid erection without treatment, typically retain the ability to orgasm, and are generally willing to try PDE5i.